Livres et « bibliothèques » dans les inventaires après décès de Salonique au XIXe siècle - Meropi Anastassiadou (Revue des Mondes Musulmans et de la Méditerranée)
In 19th century Salonica, book owners constituted - among Muslims at least - a singular category of people. This is observed when going through probate inventories kept in the Historical Archives of Macedonia in Salonica. Individuals who left some written material to their heirs - most often only a Quran - are no more than 6 to 7 % of the deceased registered in the defter-s. In this period, possessing one or more books at home was obviously something exceptional. According to the probate inventories, the rule was the absence of any contact with written texts.This remark brings up a certain number of questions. The first one concerns whether the titles of books appearing in probate inventories can teach one something about the individuals who owned them, about their intellectual interests, certainties or desires. In a different trend, the probate inventories permit the researcher to examine the social and economic profile of book owners. In 19th century Salonica, was the pleasure of reading reserved only to a few, was it a privilege linked to fortune, power or some particular professional qualifications ? The role of the book as a simple mark of knowledge, prestige and authority is also examined in this article. Above all, is not the book an emblematic object ? Is it made more to be shown off than read ? Examining the books, counting them and noting their titles is also a way to approach the society.